Expressão de genes da rota do florescimento de cana de açúcar sob influência da aplicação de Piraclostrobina na cultivar RB867515 - Silva, Vivianny Nayse Belo (2015)
The green effect with consequent productivity gains after application of Pyraclostrobin, a fungicide active ingredient, has been studied in various crops. However, the effect of this active ingredient toward genes involved in the flowering pathway in sugarcane is unknown so far. In this study, we aimed to evaluate the effect of Pyraclostrobin on ScID1, ScFT1 and ScFT2 genes found in sugarcane, RB867515 cultivar. This cultivar was grown at Muquém farm belonging to the Federal University Lavras, State of Minas Gerais. The experiment was established in randomized block design with three replications. Treatments were arranged in 2 × 3 factorial scheme consisting of two levels or doses of fungicide, and three periods (days) after fungicide application. Collections of plant material were carried out at 35, 65 and 85 days after Opera® fungicide application. Data analyses were performed by using the Rotor-Gene Series Pure Detection Software (version 2.0.2). The relative expression of a target gene was obtained by estimating the transcription efficiency and Cq deviation of an unknown sample, compared to a control, and expressed in relation to a reference gene. We found that the application of Pyraclostrobin affects the expression pattern of ScID1, ScFT1 and ScFT2 genes in the cultivar under study. For ScID1 gene, changes in terms of expression pattern occurred about 35 days after fungicide application. For ScFT1 gene, changes in terms of its expression pattern and floral inhibition occurred about 65 days after fungicide application. For ScFT2 gene, changes in terms of expression pattern occurred about 35 days after fungicide application for the treatment and control, and about 65 days after fungicide application only for the treatment. The floral inhibition for this gene occurred 65 days after fungicide application.